The effect of desire thinking on facilitating beliefs in alcohol use disorder: An experimental investigation. (9th September 2020) - Caselli, Gabriele; Gemelli, Antonella; Ferrari, Cristina; Beltrami, Daniela; Offredi, Alessia; Ruggiero, Giovanni M.; Sassaroli, Sandra; Spada, Marcantonio M.
Abstract: Permissive beliefs relate to the acceptability of engaging in alcohol use in spite of obvious potential negative consequences. They are considered the most proximal and precipitating cognitive factor in the decision to use alcohol and/or the activation of strategies to obtain it. Recent research suggested that 'desire thinking' may be involved in the escalation of craving and addictive behaviours and can play a role in strengthening permissive beliefs. The current study tested whether the induction of desire thinking would have a stronger effect on rate of conviction in permissive beliefs compared to a control cognitive response in the form of neutral thinking and whether this effect would be specific for patients with alcohol use disorder (AUD). Thirty AUD patients and 30 social drinkers (SD) were randomly allocated to two thinking manipulation tasks (desire thinking and neutral thinking). Current permissive beliefs were measured before and after manipulation and after a resting phase. Findings showed that desire thinking increased the level of current permissive beliefs after manipulation relative to the neutral thinking condition for the AUD group but not for the SD group. This effect was not purely dependent on the concurrent level of perceived craving. This study supports a causal relationship between the induction of desire thinking and rate of conviction in permissive beliefs and highlights the relevance of targeting desire thinking in the treatment for AUD patients.